An Evaluation of Clinical Nurse and Midwife Specialist and Advanced Nurse and Midwife Practitioner Roles in Ireland (SCAPE) - COYNE, IMELDA; BEGLEY, CECILY; COMISKEY, CATHERINE; HIGGINS, AGNES; LALOR, JOAN; ELLIOTT, NAOMI; SHEERIN, FINTAN (National Council for the Professional Development of Nursing and Midwifery in Ireland, 2010)
The Irish health system has moved towards a population health approach for the provision of health services and healthcare. Changing models of care delivery in tandem with the changing demographic and epidemiological profile of the population will signal the service requirements into the future. The Irish health service is driven by policy direction aiming to provide more services within primary, community and continuing care. The nursing and midwifery professions in Ireland have undergone significant change over the past decade, particularly in relation to the clinical role and responsibilities of nurses and midwives in order to provide responsive care delivery. Patient safety and risk controls necessitate on-going clinical audit, utilization of evidence-based practice, adherence to clinical guidelines, introduction of care pathways and peer review. The Report of the Commission on Nursing (Government of Ireland 1998) was the catalyst for the introduction of a clinical career pathway that would encompass progression from staff nurse or staff midwife to clinical nurse or midwife specialist to advanced nurse or midwife practitioner. The creation and development of this clinical career pathway has taken place against a background of health service reform, an integrated approach to health policy and service model implementation, and development of pre- and post-registration education and training programmes within the higher education sector and in local and regional centres of nurse and midwife education. To this end the National Council for the Professional Development of Nursing and Midwifery commissioned a joint research team from the Schools of Nursing and Midwifery, Trinity College, Dublin and the National University of Ireland, Galway through an open tender process to evaluate the role of the Clinical Nurse/Midwife Specialist and Advanced Nurse/Midwife Practitioner, focusing on the clinical and economic impact of the roles. This study, through extensive research methods, utilising a variety of data collection tools, has examined the clinical outcomes of clinical specialists and advanced practitioners in Ireland. This study has demonstrated conclusively that care provided by clinical specialists and advanced practitioners improves patient/client outcomes, is safe, acceptable and cost-neutral. Nursing and midwifery care is provided in a complex changing environment and it is critically important that resources are utilised in a cost-effective, strategic manner. The study shows the potential of clinical specialists and advanced practitioners to support implementation of health policy, meet the changing health needs of the population, address patient expectations, contribute to service reconfiguration and provide nursing and midwifery leadership for the introduction of care models and care programmes into the HSE and, potentially, other health services. Clinical specialists and advanced practitioners support a safe environment for patients by increasing the use of evidence-based clinical guidelines. Their overall positive effect on patient/client care, other staff and the health services in general is very apparent. Given these considerable benefits, and the fact that the economic analysis did not demonstrate a difference in costs between services with clinical specialists/advanced practitioners and the comparison sites, there is a strong case for introducing more clinical specialists and advanced practitioners. This Final Report and a Summary Report are available to download from our website: www.ncnm.ie I would like to thank the research teams led by Professor Cecily Begley from the School of Nursing and Midwifery, Trinity College, Dublin and Professor Kathy Murphy from the School of Nursing and Midwifery, National University of Ireland, Galway for their profes sionalism, hard work and dedication to the project. I would like to thank the Steering Committee, Valerie Small, Aveen Murray, Mary Duff and Professor Sally Redfern for their expert advice and support. Finally I would like to thank my colleagues Dr Kathleen Mac Lellan, Head of Professional Development, Dr Sarah Condell, Research Development Officer and Mary Farrelly, Professional Development Officer who continuously supported this project.
PUBLISHED
Dublin
Keywords: Midwifery